Land use Planning for the Nilgiris: Part I- Soil Conservation Survey - Basu, J K; Narayanaswamy, S; Rege, N D (Journal of Soil and Water Conservation, 2022)
Before any land is put to agriculture or other sirnilar purposes, it is of u t- most importance that its capability for such use should be exannined thoroughly and complete inventory of all (101ninant con- ditions of the land be obtained by means of survey of the area in question. A few progressive ryots know the capacity of their land for crop growth. But they normally choose to grow a particular crop which is profitable for thein irrespective of the fact whether the land is suitable for such crop or not. Faulty agricultural practices adopted by them more often accelerate soil erosion and resulting depletion in soil ferti- lity, which ultimately leads to destruction of the land. This is the story of all nations. India in general and Nilgiris in particular are not exception to this. In the Nilgiris, the topography is very rolling and steep. The rainfall is heavy and intense. Indiscriminate devegetation and deforestation for cultivation and adoption of all destructive agricultural practices have, therefore, accelerated soil erosion. This has attained so dangerous a proportion that it was found necessary to advocate among the ryots planned utilization of lands to prevent and control the growing " national menace’ the soil erosion. To evolve, therefore, a standard pattern of land capability classi- fication applicable for the district, soil con- servation survey was taken up.